Letter from Mildred Larson - Mildred Larson:::::: (1968)
A letter to members of the Western States Democratic Conference, Chairman Mildred Larson announces plans to meet in Chicago during the Democratic National Convention to conduct business and welcome new members. She proposes meeting on Friday, August 30, following the National Committee session. Agenda items include the treasurer's report, selection of the 1969 meeting site (with Denver tentatively invited), and election of officers. Larson also states that she does not wish to be considered for re-election as chairman.